"Gottheit in uns" : Die monastische und psychologische Grundlegung der Mystik nach einer überlieferten Textkollektion aus dem Werk des Šemʻon d-Ṭaibuṯeh. - Büttner, Winfried (Eichstätter Beiträge zum christlichen Orient., 2017)
The texts translated and commented on in German reveal the rich intellectual heritage and fascinating spirituality of a doctor and hermit from the end of the 7th century who lived in the Persian Beṯ Huzaye (Khusistan). Šem'on d-Taibuṯeh ("Simeon by his grace") designs an ascetic model of life in which negative experiences, self-conquest and concentration up to total withdrawal of stimuli and complete isolation from external influences gradually help to spiritual knowledge and intimate familiarity with God he describes the soul in its subtle parts as a divine dwelling and deepest expression of human likeness of God, so that there he locates the kingdom of God within man, the "deity in us". Overall, the hermit steers the course of his sources - including Gregory of Nyssa, the Macarian and Evagrian tradition, the Syrian Corpus Dionysiacum and anachoretic pioneers of his homeland - in the direction of his own brilliant contribution and lets the whole thing in different facets of a Christ-oriented mysticism of the Of the heart, of ascent, of union and deification. In addition to anatomical and physiological views, he presents a nuanced psychological model that reflects the learned environment of the monk doctor. Chronologically, again in a time of religious and political upheaval and between two phases in which the strictly diphysite churchism of its environment insists on orthodoxy, shows an extraordinary author who encountered opposition. In addition to the translated texts, this book offers a detailed analysis of the work as well as several registers that facilitate access.